Climatic favourability zones for Eucalyptus rust in Brazil - Alvares, C. A.; Sentelhas, P. C.; Mattos, E. M.; Miranda, A. C.; Moraes, W. B.; Silva, P. H.M.; Furtado, E. L. [UNESP]; Stape, J. L. (Wiley, 2017)
Brazilian forest-based industries are supported by more than 5.5 million hectares of Eucalyptus growing under different climatic conditions with different degrees of favourability for rust Puccinia psidii, including both traditional and expanding areas, where such disease is of major concern for the industry, foresters and scientists. The main objective of this study was to define favourable climatic zones for Eucalyptus rust in Brazil with the following aims: (i) to develop a spatial method for estimating the mean night-time temperature (Tng); (ii) to assess and validate a Eucalyptus rust model; and (iii) to map Eucalyptus rust favourability zones in Brazil based on the proposed model. A straightforward method, based only on latitude, day of the year, maximum and minimum air temperatures, was developed to estimate Tng, which is a key variable for a proper application of Ruiz rust model. Based on 37 field experiments with natural rust occurrence, it was observed that climatic conditions are determining factors for disease severity. Significant correlations between disease severity observed in the field and climatic conditions were found: a negative correlation with temperature (r =.50, p <.01) and a positive correlation with relative humidity (r =.89, p <.0001). A significant correlation (r =.81, p <.0001) between the normalized infection index, produced from Ruiz model, and the average rust score was also observed. Once the model was validated under field conditions, it was applied using historical average data of air temperature and leaf wetness duration to obtain monthly Eucalyptus rust favourability maps for the whole country. These final maps show that favourable climatic zones for Eucalyptus rust are extremely dynamic, with high temporal and spatial variability in Brazil and that climatic conditions should be considered for expansion of Eucalyptus to new areas, in breeding programmes, and for defining the most suitable seasons for forest establishment in each climate of the country. These results provide forestry managers with practical tools to reduce uncertainty about the expected severity of Eucalyptus rust in Brazil.